Carbon Sequestration Related to Soil Physical and Chemical Properties in the High Arctic. Issue 9 (27th August 2021) - Jílková, Veronika; Devetter, Miloslav; Bryndová, Michala; Hájek, Tomáš; Kotas, Petr; Luláková, Petra; Meador, Travis; Navrátilová, Dana; Saccone, Patrick; Macek, Petr
Abstract: Arctic soils are an important reservoir of soil organic carbon (SOC) and their role in determining arctic ecosystem functioning in global carbon budgets requires closer attention. We investigated the coupling of soil properties and SOC stabilization mechanisms in high Arctic terrestrial habitats differing in vegetation cover and organic matter input. We focused on soil physical and chemical properties in glacier foreland, soil crust, dry tundra, wet tundra, and bird cliff meadow habitats on Svalbard (Norway). Concurrently, we performed physical fractionation to determine the amount of SOC stabilized by mineral associations or occlusion in macro and microaggregates. Initial stages of soil development (glacier foreland and soil crust habitats) exhibited characteristically high bulk density and pH, and low moisture and nutrient contents, whereas more developed soils (dry and wet tundra habitats) showed opposite trends. Contrastingly, bird cliff meadow showed low bulk density, intermediate moisture, and very high nutrient content. The amount of SOC stabilized by mineral associations and occlusion in aggregates generally increased with vegetation cover; hence, the more developed habitats supported higher contents of stabilized SOC. However, SOC was stabilized in aggregates even in initial stages of soil development. SOC content in most fractions correlated positively with contents of dissolved organic carbon and nitrogen, suggesting that both dissolved organic carbon and nitrogen might have provided some degree of SOC stabilization through increased formation of aggregates and suppression of microbial mineralization of soil organic matter, respectively. Our findings underscore the notion that models of SOC sequestration in the Arctic should account not only for total SOC content, but also SOC stabilization mechanisms, as represented by SOC content in respective soil fractions. Key Points: Soils of initial habitats exhibited high bulk density and pH, and low moisture and nutrient contents as opposed to soils of developed habitats Content of soil organic carbon (SOC) stabilized by occlusion in aggregates or by adsorption on mineral particles generally increased with vegetation cover, hence more developed habitats provide a large degree of SOC stabilization SOC content in most of the fractions positively correlated with dissolved organic C as well as dissolved N content